Educating the whole person: Broad extracurricular involvement and prevalence of purpose and thriving among college students in China - Zhang, Wenling; Mariano, Jenni Menon; Zhu, Mo; Jiang, Fei (Frontiers in Psychology, 2022)
College students in China can choose from a wide variety of university organized extra-curricular activities (EAs), which are intended to enrich and deepen the learning experience, and reflect an educational policy goal to cultivate the whole and well-rounded person. These activities are also consistent with another policy goal, which is to foster optimal student outcomes like life purpose development. This study examined associations between EA involvement and life purpose and associations between EA and thriving attributes of resourcefulness/resilience and life satisfaction among 332 undergraduate students enrolled at 20 universities across China. Measures of EA involvement, purpose resourcefulness/resilience, and life satisfaction were adapted to the Chinese culture, language, and student population. Four clusters of students emerged, representing varying degrees of well-roundedness according to their EA involvement. Patterns of associations examined between and within clusters supported the general hypothesis that more frequent and well-rounded EA involvement is positively associated with purpose and life-satisfaction, but not with resilience/resourcefulness. The significance of the findings for future research and practice are discussed.